Exploring Cruise Tourists’ Preferences and Satisfaction: The Case of Taiwan - Min-Yen Chang (MDPI AG, 2021)
In this study, the product attributes of cruise tours are distinguished into on-board activities, leisure space, cabin comfort, Michelin restaurant, and refund mechanism, and the multi-attribute utility model of cruise tours is constructed using the choice experiment (CE) method. Of the 575 questionnaires distributed, 439 were valid, with an effective recovery rate of 76.3%. The results revealed the following: (1) when cruisers travel, what they value the most is the quality of service on board, followed by the facilities on board; (2) passengers’ preferences for comfortable pool space and more activities on board are negatively significant, indicating that they do not prefer to add these amenities and experiences to the cruise ship; (3) passengers are willing to pay extra to upgrade the interior cabin to one with a view and to experience the Michelin restaurant; and (4) influenced by the COVID-19 pandemic, cruisers are more willing to manage their own health. Moreover, the pandemic does not reduce their willingness to travel by cruise.